Evaluation of Online Learning for Inclusive Junior High School Students - Tyas Ratnawati; Rugaiyah Rugaiyah; Siti Rochanah (STAI Hubbulwathan Duri, 2021)
Online learning has been carried out by all levels of education, starting from elementary school to higher education, applied to traditional and inclusive schools. The purpose of the study was to obtain the results of online learning evaluations for inclusive students at State Junior High Schools 36 Jakarta. This study used a descriptive analytical-qualitative approach. Data were collected through observation, interviews, documentation, and group discussion forums. Data analysis techniques consist of data reduction, data presentation, conclusion drawing/verification. The study results concluded that the implementation of online learning was carried out regularly by government standards in terms of planning, implementation, and evaluation. The students also did not experience any problems and were diligent in participating in online learning activities because of parental assistance. The study results also have implications for understanding the concept of cooperation between the school and parents in carrying out online learning activities so that students can take online classes regularly.